Skilful Seasonal Predictions of Summer European Rainfall. Issue 7 (2nd April 2018) - Dunstone, Nick; Smith, Doug; Scaife, Adam; Hermanson, Leon; Fereday, David; O'Reilly, Chris; Stirling, Alison; Eade, Rosie; Gordon, Margaret; MacLachlan, Craig; Woollings, Tim; Sheen, Katy; et al.
Abstract: Year‐to‐year variability in Northern European summer rainfall has profound societal and economic impacts; however, current seasonal forecast systems show no significant forecast skill. Here we show that skillful predictions are possible ( r ~0.5, p  < 0.001) using the latest high‐resolution Met Office near‐term prediction system over 1960–2017. The model predictions capture both low‐frequency changes (e.g., wet summers 2007–2012) and some of the large individual events (e.g., dry summer 1976). Skill is linked to predictable North Atlantic sea surface temperature variability changing the supply of water vapor into Northern Europe and so modulating convective rainfall. However, dynamical circulation variability is not well predicted in general—although some interannual skill is found. Due to the weak amplitude of the forced model signal (likely caused by missing or weak model responses), very large ensembles (>80 members) are required for skillful predictions. This work is promising for the development of European summer rainfall climate services. Key Points: First evidence is found for skillful seasonal predictions of Summer Northern European rainfall Model convective rainfall variability is the primary source of skill, while dynamical circulation is still poorly predicted Large ensembles are required to achieve skillful rainfall forecasts